Clinical manifestation of blepharocheilodontic (BCD) syndrome: a case review - Navasheilla Retna .R; Sockalingam .S.N.M.P (Universiti Kebangsaan Malaysia, 2013)
BCD syndrome is a rare birth syndrome characterised by cleft lip and palate, euryblepharon with/without limb anomalies, ectropion of lower eyelids and hypertelorism. The dental anomalies include cone shaped microdontic teeth and oligodontia. Different combinations of these signs have been found sporadically in patients. This syndrome is also known as Elschnig’s syndrome. By at large, patients with this syndrome have no potentially fatal anomalies. Their growth and development were usually normal. This case review described the clinical manifestation and oral findings of a patient with BCD syndrome. The dental need of the patient was outlined.